Effect of match factors on the running performance of elite female soccer players - Trewin, J.; Meylan, C.; Varley, M. C.; Cronin, J.; Ling, D. (The Journal of Strength and Conditioning Research, 2018)
The purpose of this study was to examine the effects of match factors on the match running of elite female soccer players. Players from the same women's national team (n = 45) were monitored during 47 international fixtures (files = 606) across 4 years (2012-2015) using 10-Hz global positioning system devices. A mixed model was used to analyze the effects of altitude, temperature, match outcome, opposition ranking, and congested schedules. At altitude (>500 m), a small increase in the number of accelerations (effect size [ES] = 0.40) and a small decrease in total distance (ES = -0.54) were observed, whereas at higher temperatures, there were decreases in all metrics (ES = -0.83 to -0.16). Playing a lower ranked team in a draw resulted in a moderate increase in high-speed running (ES = 0.89), with small to moderate decreases in total distance and low-speed running noted in a loss or a win. Winning against higher ranked opponents indicated moderately higher total distance and low-speed running (ES = 0.75), compared with a draw. Although the number of accelerations were higher in a draw against lower ranked opponents, compared with a win and a loss (ES = 0.95 and 0.89, respectively). Practitioners should consider the effect of match factors on match running in elite female soccer.